Electronic Method (Pro-Kin) for Improving and Speeding Up the Recovery After Ankle Sprain - Marvulli, Riccardo; Ianieri, Giancarlo; Pignatelli, Giovanni; Santagati, Dario; Ranieri, Maurizio; Megna, Marisa (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Background and Objective: Ankle sprains, very common injuries occurred especially during sports activities, are mainly caused by indirect trauma, which influences exaggerated stress exceeding the strength of stabilization mechanisms. Up to 85% of such injuries result from a sudden flexion and inversion of the foot. In this study, we analyzed the effectiveness of the platform Pro-kin, an innovative system that has given us the possibility to combine the functionality of the older proprioceptive boards with very accurate software in order to improve and accelerate the recovery after ankle injuries. Methods: 30 patients with moderate ankle sprain outcomes in two groups (A and B) were included in this study. Group A was only treated with proprioceptive exercises for 3 weeks, while the group B was trained with the innovative Pro-kin. In both groups, we evaluated VAS scale, the ratio between the number of circumductions performed by the injured foot and the time spent on doing them and the percentage of load among the injured and the healthy foot in statics and dynamics with electronic baropodometry. Our data has been collected at t0 (beginning of study), t1 (one week later), t2 (two weeks later), t3 (one month later), t4 (two months later), and then analyzed by the two-way analysis of variance (2-way ANOVA) test. Results: At t0 no statistical differences of pain in the 2 groups (3.3 and 3.4); the values were similar, as well as at time t1, t2, t3 and t4. Therefore we deduce that Pro-kin treatment is not painful. The number of circumductions performed was definitely better in B group since the first week; for the A group the values considerably increased only at t3 (one month later). Comparing the load percentages on two feet detected by the electronic baropodometer in statics and in dynamics, we deduced that the patients of A group tend to lean mostly on the healthy foot than B group. Conclusion: This study demonstrates that new technological resources (such as Pro-kin) may be helpful to improve and speed up the recovery of ankle sprain in athletes.
Keywords: electronic software platform